Uma discussão sobre a base metafórica das figuras de linguagem - Seves, Giovana Franco [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The aim of this work is the analysis of some figures of speech, which is based on the existence of a nature of metaphorical process. The research starts from the hypothesis that these figures form themselves by this process. The study is based on the reading of the chapter “Figuras de linguagem”, which is in the work Lições de gramática de usos do português (NEVES, in the press), in which are given lessons about figures of speech, using literary texts and suggesting a metaphorical base for the general sustenance of the analyses. From these lessons, that had already directed groupings and analyses in Seves (2009), a reanalysis was done according to a theoretical orientation which basis is cognitivist, what contribute to this idea about the origin of the figurative processes. The bases of the theoretical orientation, in this sense, are: the conceptual metaphor theory (LAKOFF; JOHNSON, 1980), which considers metaphor as a cognitive (mental) process; and the current of the systematic metaphor (CAMERON, 2005 apud SARDINHA, 2007) that defends the attention to the recurring use of metaphor in real language, before doing assertions about the mind’s functioning. The analyses indicated these conclusions: a) the theory of the conceptual metaphor can be considered efficient for the foundation of the analyses, what implies a minimization of the metonymic component in the exam of these figures; b) and in the basis of the majority of the founded figures it is evident the nature of a metaphorical process

O presente trabalho tem como objetivo a análise de determinadas figuras de linguagem, com base na natureza do processo metafórico, partindo-se da hipótese de que elas se configuram por meio desse processo. A inspiração do trabalho foi a leitura do capítulo “Figuras de linguagem”, da obra Lições de gramática de usos do português (NEVES, no prelo), em que se dão lições sobre figuras de linguagem por meio de textos literários, invocando-se uma base metafórica para a sustentação geral das análises. A partir dessas lições, que já direcionaram agrupamentos e análises em Seves (2009), buscou-se uma reanálise das figuras segundo um direcionamento teórico de base cognitivista que corrobora essa concepção da origem dos processos figurativos. As bases de direcionamento teórico, nesse sentido, são: a teoria da metáfora conceptual (LAKOFF; JOHNSON, 1980), que preconiza a metáfora como um fenômeno cognitivo (mental); e a corrente da metáfora sistemática (CAMERON, 2005 apud SARDINHA, 2007), que defende a atenção ao uso recorrente da metáfora na linguagem real, antes de se fazerem alegações sobre o funcionamento da mente. As análises apontaram para as seguintes conclusões: a) a teoria da metáfora conceptual pode ser considerada eficiente para o embasamento das análises, o que implica uma minimização do componente metonímico na avaliação dessas figuras; b) e, comprovadamente, na base da maioria das figuras encontradas está evidente a natureza de um processo metafórico
Keywords: Figuras de linguagem; Metafora; Metonimias; Base metafórica; Base metonímica; Metáfora conceptual; Metáfora sistemática